A Systematic Review of the Chinese-English Translation of Public Signs. (April 2022) - Amenador, Kate Benedicta; Wang, Zhiwei
To understand the current status of Chinese-English public sign translation research in China, we analyzed 137 published studies in the past 15 years and found that public sign translation research in China has developed progressively from the nascent stage in 2005 to its climax in 2014 and then began to decline to date. Public signs translation research has attracted the attention of many scholars, and fruitful results have been achieved in terms of research content, which covers the definition, features, functions, translation errors, translation principles, strategies, and the theories applied to C-E public signs translation. However, there are still many deficiencies in related research, such as the repetition of research content, the limited scope of investigation, and the lack of a clear distinction between what constitutes a feature and a translation principle of public signs. The study suggests that future research content on public sign translation should be in-depth and more diversified. Also, more public sign translation experts should be trained to improve their translation quality, and the related supervisory body should intensify their supervision. Future researchers should extend their investigations to include other public signs in thematic areas such as menus, museums, folk gardens, culture-specific items, and theory development as studies in these areas are limited. It is hoped that the research findings will offer insight into the problems and gaps in related research and help facilitate the development of relevant language policies, translation theories, and methods for the translation and study of public signs.